MOTIF DAN KEPUASAN REMAJA KOTA DENPASAR MENONTON TAYANGAN HOTMAN PARIS SHOW MELALUI YOUTUBE - Subudi Darma, Made Dwi; Dewi Pascarani, Ni Nyoman; Pradipta, Ade Devia (E-Jurnal Medium, 2019)
ABSTRACT   Hotman Paris Show is a talk show program that is aired on iNews TV and also had a large audience on YouTube. This study aimed to find out what the R motive and how the satisfactionRof teenager in the city ofFDenpasar in watching Hotman Paris Show. This research used the theory of E Uses and Gratifications and used D descriptive quantitative method. Sampling F technique in this research was S purposive sampling. Data were F obtained by distributing questionnaires F using Likert scale. The A analytical technique used d is descriptive statistics by looking at the m mean score of motives and s satisfaction. The results showed D that there are one motives that can be s satisfied in watching t the Hotman Paris Show that is the motif of information. Motives that can not be satisfied in watching the Hotman Paris Show is the motive of personal identity ,integrity and social interaction and the motive F of entertainment.   Keywords : Denpasar, Hotman Paris Show, Motive, Satisfaction